Study on the mechanism of using IR illumination to improve the carrier transport performance of CdZnTe detector. (6th March 2018) - Mao, Yifei; Zhang, Jijun; Lin, Liwen; Lai, Jianming; Min, Jiahua; Liang, Xiaoyan; Huang, Jian; Tang, Ke; Wang, Linjun
Abstract: Different wavelength IR light (770–1150 nm) was used to evaluate the effect of IR light on the carrier transport performance of CdZnTe detector. The effective mobility-lifetime product ( μτ *) of CdZnTe achieved 10 −2 cm 2 V −1 when the IR wavelength was in the range of 820–920 nm, but decreased to 1 × 10 −4 cm 2 V −1 when the wavelength was longer than 920 nm. The mechanism about how IR light affecting the carrier transport property of CdZnTe detector was analyzed with Shockley–Read–Hall model. The defect of doubly ionized Cd vacancy ([VCd ] 2− ) was found to be the main factor that assist IR light affecting the μτ of CdZnTe detector. The photoconductive experiment under 770–1150 nm IR illumination was carried out, and three kinds of photocurrent curve were detected and analyzed by solving the Hecht equation. The experiments demonstrated the effect of [VCd ] 2− defect on the carrier transport property of CdZnTe detector under IR illumination.